S100a8/a9 Signaling Causes Mitochondrial Dysfunction and Cardiomyocyte Death in Response to Ischemic/Reperfusion Injury. Issue 9 (27th August 2019) - Li, Yulin; Chen, Boya; Yang, Xinying; Zhang, Congcong; Jiao, Yao; Li, Ping; Liu, Yan; Li, Zhenya; Qiao, Bokang; Bond Lau, Wayne; Ma, Xin-liang; Du, Jie
Abstract : Background: Myocardial ischemia-reperfusion (MI/R) injury is a significant clinical problem without effective therapy. Unbiased omics approaches may reveal key MI/R mediators to initiate MI/R injury. Methods: We used a dynamic transcriptome analysis of mouse heart exposed to various MI/R periods to identify S100a8/a9 as an early mediator. Using loss/gain-of-function approaches to understand the role of S100a8/a9 in MI/R injury, we explored the mechanisms through transcriptome and functional experiment. Dynamic serum S100a8/a9 levels were measured in patients with acute myocardial infarction before and after percutaneous coronary intervention. Patients were prospectively followed for the occurrence of major adverse cardiovascular events. Results: S100a8/a9 was identified as the most significantly upregulated gene during the early reperfusion stage. Knockout of S100a9 markedly decreased cardiomyocyte death and improved heart function, whereas hematopoietic overexpression of S100a9 exacerbated MI/R injury. Transcriptome/functional studies revealed that S100a8/a9 caused mitochondrial respiratory dysfunction in cardiomyocytes. Mechanistically, S100a8/a9 downregulated NDUF gene expression with subsequent mitochondrial complex I inhibition via Toll-like receptor 4/Erk–mediated Pparg coactivator 1 alpha/nuclear respiratory factor 1 signaling suppression. Administration of S100a9 neutralizing antibody significantly reduced MI/R injury and improved cardiac function. Finally, we demonstrated that serum S100a8/a9 levels were significantly increased 1 day after percutaneous coronary intervention in patients with acute myocardial infarction, and elevated S100a8/a9 levels were associated with the incidence of major adverse cardiovascular events. Conclusions: Our study identified S100a8/a9 as a master regulator causing cardiomyocyte death in the early stage of MI/R injury via the suppression of mitochondrial function. Targeting S100a8/a9-intiated signaling may represent a novel therapeutic intervention against MI/R injury. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT03752515 Abstract : Supplemental Digital Content is available in the text.